Nerve Conduction study in healthy individuals, a preliminary age based study - Thakur, D; Paudel, B H; Jha, C B (Kathmandu University Medical Journal, 2012)
Background Nerve conduction study assesses peripheral nerve functions and has clinical implication. Objectives To study the effect of age on nerve conduction study variables in healthy adults. Methods Cross sectional study was done from Jan 2006 to Dec 2006 in department of Physiology, BP Koirala Institute of Health Sciences, Dharan, Nepal. The study was done in 34 (younger, n= 18, 17 to 29 years; older, n= 16, 30 to 57 years) consenting healthy adults of either sex. The compound muscle action potential and sensory nerve action potential were recorded using standard technique. Due to the non-normal distribution of data, the effect of age on nerve conduction study variables was analyzed using Mann Whitney U test. Results Younger vs. older individuals: older had lower Compound Muscle action potential amplitude (mV) in all motor nerves except radial and left ulnar nerves. Compound Muscle action potential duration (ms) was shorter in older (p<0.05) in ulnar, tibial, right median and left common peroneal motor nerves than the younger: right median (6.92±1.3 vs. 8.5±1.88), right ulnar (7.09±1.54vs. 8.2±1.31), left ulnar (10.56±1.44 vs. 12.06±1.5), right tibial (6.28±0.81vs. 7.28±1.12), and left tibial (9.58±1.52vs.10.78±1.71). Sensory nerve actional potential amplitude (?V) was smaller in older as compared to younger: right median (19.01±7.83 vs. 26.97±10.63), right ulnar (10.9±3.44 vs.16.09±5.85) and right radial (14.31±4.34 vs.19.72±6.47). SNAP duration (ms) was longer in older: right ulnar (1.34±0.17 vs.1.26± 0.18), left ulnar (1.46±0.14 vs. 1.29±0.26), and left median (1.11± 0.14 vs. 1± 0.14). Conclusions Age has definite effects on amplitude and duration of motor and sensory nerves. Different nerves have different timing of aging. Without adjustment for age, the sensitivity and specificity of nerve conduction study will decrease whenusing the same reference data in patients with different age. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6218 Kathmandu Univ Med J 2010;8(3):311-6